The Mutation Analysis of the AMT Gene in a Chinese Family With Nonketotic Hyperglycinemia - Zhou, Bing-bo; Hui, Ling; Zhang, Qing-hua; Chen, Xue; Zhang, Chuan; Zheng, Lei; Feng, Xuan; Wang, Yu-pei; Ding, Zhong-jun; Chen, Rui-rong; Ma, Pan-pan; Liu, Fu-rong; et al. (Frontiers in Genetics, 2022)
Background: Nonketotic hyperglycinemia is a metabolic disease with autosomal recessive inheritance due to the glycine cleavage system (GCS) defect leading to the accumulation of glycine that causes severe and fatal neurological symptoms in the neonatal period. Methods: Genomic DNA was extracted from the peripheral blood of the female proband and her family members. The AMT variation was detected in the patient by whole-exome sequencing (WES), and the variant was validated by Sanger sequencing. Results: The WES showed that there were novel compound heterozygous frameshift variations c.977delA (p.Glu326Glyfs*12) and c.982_983insG (p.Ala328Glyfs*22) in exon eight of the AMT gene (NM_000481.4) in the proband. Genetic analysis showed that the former was inherited from the mother, and the latter was inherited from the father. Conclusion: We report the novel compound heterozygous variation of the AMT gene in a Chinese girl with NKH by WES, which has never been reported previously. Our case expanded the AMT gene mutation spectrum, further strengthened the understanding of NKH, and deepened the genetic and clinical heterogeneity of the disease. However, the study of treatment and prognosis is still our future challenge and focus.